The impact of growth mindset on subjective wellbeing in elementary school students: a moderated mediation model - Lingyi Peng; Lingyi Peng; Huohong Chen; Wei Liang; Wei Liang; Zifu Shi; Qiaoping Li (Frontiers in Psychology, 2025)
IntroductionThis study examines the relationship between growth mindset and subjective wellbeing among elementary school students, with a focus on the mediating role of academic self-efficacy and the moderating role of perceived teacher support.MethodsUtilizing the cluster sampling method, a sample of 1,740 elementary school students completed measures assessing growth mindset, subjective wellbeing, academic self-efficacy, and perceived teacher support.ResultsThe results show that: (1) growth mindset positively predicts elementary school students' subjective wellbeing; (2) academic self-efficacy partially mediates the association between growth mindset and elementary school students' subjective wellbeing; and (3) perceived teacher support moderates the first stage of the mediation pathway, such that the positive effect of growth mindset on elementary school students' academic self-efficacy is stronger under high levels of perceived teacher support.DiscussionThese findings indicate that growth mindset influences elementary school students' subjective well-being both directly and indirectly through academic self-efficacy. Moreover, the impact of growth mindset on academic self-efficacy is stronger among elementary school students with higher perceived teacher support.